2016
DOI: 10.1175/jcli-d-15-0820.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Observed Relationships between Variability in Gulf Stream Sea Surface Temperatures and the Atmospheric Circulation over the North Atlantic

Abstract: The advent of increasingly high-resolution satellite observations and numerical models has led to a series of advances in understanding the role of midlatitude sea surface temperature (SST) in climate variability, especially near western boundary currents (WBC). Observational analyses suggest that ocean dynamics play a central role in driving interannual SST variability over the Kuroshio–Oyashio and Gulf Stream extensions. Numerical experiments suggest that variations in the SST field within these WBC regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 36 publications
9
54
0
Order By: Relevance
“…For example, research exploring the monthly variability of precipitation over Europe identified a significant contribution from evaporation over land (Zveryaev and Allan, ), which could imply preconditioning in terms of both soil moisture and periods of drought. The significant impact of the atmospheric teleconnections identified herein, together with the role of SST variability on convective activity in Europe, similar to recently noted interactions (Piazza et al ., ; Wills et al ., ), motivates further analysis to explore both the joint variability along with other drivers of atmospheric–oceanic variability over the region that may be more remote, such as El Niño/Southern Oscillation (ENSO: cf. Lee et al ., ; Allen et al ., ; Cook et al ., ; Molina et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, research exploring the monthly variability of precipitation over Europe identified a significant contribution from evaporation over land (Zveryaev and Allan, ), which could imply preconditioning in terms of both soil moisture and periods of drought. The significant impact of the atmospheric teleconnections identified herein, together with the role of SST variability on convective activity in Europe, similar to recently noted interactions (Piazza et al ., ; Wills et al ., ), motivates further analysis to explore both the joint variability along with other drivers of atmospheric–oceanic variability over the region that may be more remote, such as El Niño/Southern Oscillation (ENSO: cf. Lee et al ., ; Allen et al ., ; Cook et al ., ; Molina et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…6e), in which the baroclinic vertical structure of the u response is evident. The significant positive u anomaly of 0.2-0.3 K extends up to 300 hPa and is accompanied by the ascending motion (Czaja and Blunt 2011;Smirnov et al 2015;Wills et al 2016), while the significant negative u anomaly of 0.2-0.3 K up to 600 hPa is coincident with the descending motion. The deeper extension of the diabatic heating than the cooling is consistent with the finding by Révelard et al (2016), who attributed the uneven vertical distribution of the heating and cooling to the primary cause of the nonlinearity in observed circulation response to the changes in the Kuroshio Extension front (Qiu et al 2014).…”
Section: Vertical Distribution Of the Responsementioning
confidence: 94%
“…However, Frankignoul et al (2001) found no evidence that the GS SST anomaly exerts a direct impact on the large-scale circulation. In contrast, Wills et al (2016) identified the significant transient atmospheric circulation responses that lag the SST anomalies in the GS extension by several weeks, with the pattern of response characterized by the anomalous low (high) sea level pressure (SLP) over the GS region (south of Iceland). Similarly, O'Reilly et al (2017) found the northward shift of the North Atlantic eddy-driven jet and the increase in European blocking frequency in response to the GS SST front (see also O'Reilly et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the sharp SST front plays an important role in the occurrence of European winter-time blockings (O'Reilly et al 2016). Using ERAInterim data, it was shown that warm SST anomalies in the Gulf Stream region can be connected to anomalous anticyclonic atmospheric circulation anomalies over the Gulf Stream extension several weeks before, advecting warm air northward across the (climatological) SST gradient (Wills et al 2016). A linearly independent anticyclonic anomaly south of Iceland can be found lagging these SST anomalies by 10-20 days and likely reflects the atmospheric response to the anomalous SST forcing.…”
mentioning
confidence: 99%